The place of emotional intelligence in the ‘intelligence’ taxonomy: crystallized intelligence or fluid intelligence factor? - Wn Husin, Wan Nurul Izza; Nordin, Mohamad Sahari (Elsevier, 2013)
Despite over two decades of research, the construct of emotional intelligence (EI) remains elusive as recent researchers debate whether it can be considered a new form of „intelligence‟ that fulfils the standard of an intelligence construct. The main objective of this study is to assess the place of emotional intelligence within the existing major factors of intelligence, particularly fluid intelligence (gf) and crystallized intelligence (gc). Second, it investigated the convergent validity of emotional intelligence when correlated with general cognitive intelligence (g). The Shipley-2 IQ test and the WEIS performance-based EI test were administered to 422 respondents. The results from the confirmatory factor analyses utilizing structural equation modelling (SEM) revealed that emotional intelligence does not adequately fit the intelligence taxonomy. Meanwhile, the relatively small EI/g correlation revealed that the WEIS is not a pure ability measure. Therefore, more research and the development of new EI measures are required to determine whether EI has an intelligence component.